Need Analysis to Develop Alternative Energy E-Student Worksheet Integrated Inquiry Learning and Local Wisdomto Facilitate Students' Critical Thinking Skills - Tiara Julia; Emiliannur Emiliannur; Hidayati Hidayati; Renol Afrizon (Jurnal Penelitian Pembelajaran Fisika, 2026)
This study aims to develop an E-Student Worksheet on alternative energy integrated with Inquiry Based Learning (IBL), local wisdom, and Canva AI to facilitate the critical thinking skills of Phase E senior high school students. This research is motivated by the low level of students' critical thinking skills, limited digital teaching materials, and difficulties in understanding physics concepts. To address these challenges, a digital E-Student Worksheet was developed by integrating inquiry-based activities, local wisdom of West Pasaman, and interactive Canva AI features. This study employed the Research and Development (R&D) method using the 4D model, consisting of Define, Design, Develop, and Disseminate stages. Research data were collected through preliminary studies, student needs questionnaires, teacher interviews, and validity and practicality assessments. The preliminary study showed that students' critical thinking skills were relatively low, with an average achievement of 49.70%. The developed E-Student Worksheet is expected to serve as a valid and practical digital learning resource that facilitates students' critical thinking skills in physics learning